Comparative morphological and morphometrical studies on the kidney in broiler chicken and broiler duck - K.P. Deepa; A.R. Sreeranjini; C.B. Soumya (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was conducted on the kidneys of six each of adult broiler chicken and broiler ducks. The colour of kidney in chicken was reddish brown while in duck it was slightly greyish. In both broiler chicken and broiler duck, each kidney was incompletely divided into three lobes; cranial, middle and caudal of which caudal lobes were the largest. The shapes of kidney lobes in broiler chicken and duck showed some differences. The kidneys of broiler duck were larger than that of broiler chicken. Length of three lobes on both sides in chicken showed significant difference (P